POLA PERINGKAT SISWA BERDASARKAN TOTAL NILAI PENGETAHUAN DAN KETERAMPILAN: Studi Deskriptif di Madrasah Ibtidaiyah Nahdlatul Ulama Manbaul Huda Undaan Kudus - Supriyanto, Supriyanto (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
This study aims to explore the ranking patterns of students based on the total scores of knowledge and skills at MI NU Manbaul Huda, Undaan, Kudus. The methodology used is a quantitative descriptive approach with stratified random sampling technique, involving 37, fourth-grade, five-grade and sixth-grade students. Data were collected through questionnaires and score documents, and analyzed using SPSS version 25.0 software. The findings indicate a significant relationship between the total scores of knowledge and skills with students' rankings, where the total knowledge score has a greater influence. The average knowledge score of students is 78.5, while the average skills score is 75.3, indicating a gap in the mastery of practical skills. This study concludes that the existing ranking system needs to be improved to create a balance between the assessment of knowledge and skills, thus encouraging students to excel in both aspects. These findings are expected to provide insights for educators and policymakers in designing a more effective and fair assessment system.